(untitled) (Observatorio Económico, 2017)
Although school segregation in Chile is a recurring topic on the public agenda, the emphasis is generally placed on student selection and the lack of "mixing" among students from different socioeconomic levels. Without downplaying the importance of the issue, if the education students receive were of similar quality, the effect of such segregation would be limited to the lack of interaction among groups and to the few job-access networks (which in Chile’s case tend to be relevant) available to them. Continue reading...